BRIDGING CSR AND SOCIAL ENTREPRENEURSHIP: A CASE STUDY OF COMMUNITY EMPOWERMENT IN INDONESIA’S MINING SECTOR - Harry Z Soeratin; Sakroni Sakroni (Adisam Publisher, 2025)
This paper explores the strategic linkage between Corporate Social Responsibility (CSR) and social entrepreneurship as an innovative approach to generating sustainable social impact. Employing a case-study method focused on a coal-mining company in Indonesia, the study illustrates how CSR functions not merely as a matter of compliance or philanthropy, but as a tool for community empowerment through capacity building and local enterprise development. The findings reveal that CSR initiatives oriented toward strengthening social entrepreneurship—such as skills training, micro-enterprise development, and women’s empowerment—can create mutually reinforcing social and economic value. Nonetheless, challenges related to sustainability, program monitoring, and competency enhancement remain critical issues that must be addressed. The study recommends integrating social-entrepreneurship approaches into corporate CSR strategies and fostering multi-stakeholder partnerships to broaden their impact. Theoretical and practical implications are discussed, along with suggestions for future research aimed at bolstering external validity and the generalizability of findings within the context of sustainable development.